Framework for the implementation of a supplier Kanban System in a small and medium scale industry - Pirabarkaran, Ponniah (2019)
The framework for the implementation of Supplier Kanban System was developed as a simple step-by-step guide for small and medium-sized companies (SMEs) with limited resources that wish to implement the system for an extended period of time. The model takes into consideration of the limited resources of manpower, time and money available to the SME companies and allows the companies to freely select only some (if not all) of the elements of the system, and apply it at their own comfortable pace. The framework was developed using an Action Research model which consists of two parts: (i) the core action research project, and (ii) the thesis action research project. The core action research project was undertaken to solve the supply chain and warehouse management problem in APMAE, the company where the research was carried out. The thesis action research project developed the Framework for the Supplier Kanban System by combining the knowledge, learning and experience gained from both the projects. The research was conducted over the four Action Research Cycle and Continuous Learning Cycles for a period of three years and the methods used to collect data were participant observations, participant interviews, focus group interviews, diary keeping and document research. The outcome from the core action research project was a twenty nine percent reduction in inventory and a thirty percent reduction in manpower resulting in a successfully implemented Supplier Kanban System in APMAE. The outcome from the thesis action research project is the framework for the implementation of a Supplier Kanban System.